(untitled) (Oxford, 2008)
Visitor attractions represent a complex sector of the tourism industry and are the catalytic focus for the development of tourism infrastructure and services. As this area grows, there are still many questions to be answered and issues to be understood – such as what visitor attractions actually are, what forces drive their development, who visits them and why, how they are funded, and what the numerous day-to-day challenges are in respect of their management and marketing. The second edition of this successful text investigates these issues further and provides more solutions and suggestions for the present and future. In its 2nd edition, Managing Visitor Attractions: New Directions has been fully revised and updated to include new case studies on attractions in Singapore, seasonal variation,religion-based attractions, HRM issues and heritage tourism. It also includes five new chapterslooking at attraction success and failure, interpretation, school excursions, managing gardensand brand management.
Keywords: Du lịch,Giải trí,Tourism,Recreation; Quản lý,Quản lý,Management,Management